Pengembangan Media Pembelajaran Video Pengamatan pada Mata Pelajaran Praktikum Akuntansi Lembaga/Pemerintah Kelas XI Akuntansi di SMK Negeri Surabaya - Cerelia Amanda Arifiyani; Susanti Susanti (Jurnal Pendidikan Akuntansi (JPAK), 2020)
Indonesia currently adopts the 2013 revised 2018 curriculum which is expected to be able to improve education from the aspect of knowledge, aspect of skills, and aspects of attitudes and behavior. One of learning models that best fits the 2013 revised curriculum is the learning model with the scientific approach. The observing stage is the initial phase in the scientific approach so that it becomes the most important support capable of providing meaning in the learning process (meaningful learning). Observation activities in learning that are often encountered are reading and listening to modules, books, and pictures. In addition, the Institutional / Government Accounting Practicum is a new subject whose learning media is currently very limited, some of the existing media contain material with instruments that are not in accordance with basic competencies, and the sources used are not reliable. Therefore, the researcher developed a special learning media for the Institute / Government Accounting Practicum subject in accounting SMK. The development model used is ADDIE, the resulting media will be validated by 2 material expert and media expert. The results of validation from material experts get an average percentage value of 87.6% with the interpretation criteria "Very Appropriate" and media experts of 96% with the criteria "Very Appropriate". The overall results of the validation material and media experts get an average score of 91.8%, so that it can be said the media developed is very suitable for use on observing activities while teaching and learning.